Serum Biomarkers for Diagnosis Drug Resistance Tuberculosis: A review - Towifah Fauziah Choerunisa (Sean Institute, 2026)
Multidrug-resistant tuberculosis (MDR-TB) poses a significant challenge to global health. Current gold-standard diagnostic methods, such as culture, GeneXpert, and line probe assays, facing limitations including high costs, long processing times, and reliance on sputum samples. These challenges have driven the search for serum biomarkers for diagnostic approach. Serum biomarkers offer the potential for rapid and scalable diagnosis, especially for patients unable to produce sputum. This review synthesizes findings on key serum biomarkers, categorizing them into cytokines, oxidative stress markers, metabolic indicators, lipids, and genetic elements such as long non-coding RNAs and miRNAs. These biomarkers highlight the complex immune, metabolic, and molecular adaptations in MDR-TB, offering enhanced diagnostic precision and treatment monitoring capabilities. Future prospects include the development of cost-effective assays, large-scale validation studies, and the integration of multi-biomarker panels with advanced computational tools